Model for route planning of freight buses. - Zheng, Chang; Yue, Qian; Song, Hu; Yuqing, Liu; Yan, Song (SHS Web of Conferences, 2024)
This paper introduces freight buses as a novel solution for city logistics, aiming to replace other freighters currently operated by various private logistics firms within city centers. The focus lies on investigating the route planning challenge associated with integrating freight buses into an city distribution framework. Each freight bus follows a predefined route, repeatedly traversing from a distribution center to multiple depots before returning to the distribution center. All depots are serviced by multiple freight buses on a consistent basis. This route planning problem presents a fresh iteration of the periodic vehicle routing problem. To tackle this challenge, the paper proposes a Mixed-Integer Linear Programming model, serving as a fundamental framework for future research endeavors concerning freight buses.